A point cloud analysis method for high-voltage breakdown and creepage inside metal-encapsulated system-in-package - Wang Lu; Bai Han; Zeng Yanping; Ding Taojie (Dianzi Jishu Yingyong, 2024)
This paper combines high-precision modeling and graph theory ideas to establish a novel reliability analysis method, which provides a strong guarantee for product design and testing, for analyzing the potential risk of breakdown and creepage inside the high-voltage isolated system-in-package products. Firstly, the 3D model of the product is converted into a point cloud model, and a computable numerical model is formed through filtering and surface reconstruction. Then, according to the geometric characteristics and physical relations, the surface creepage problem and breakdown problem are equivalent to the calculation of geodesic path and Euclidean path, respectively. According to the layout, the Dijkstra algorithm is optimized to calculate the breakdown and creepage paths after packaging. Finally, the product risk level is judged by reference to the experimental standards.